Review of novel functions and implications of circular RNAs in hepatocellular carcinoma - Liu, Zheng; Yang, Fangming; Xiao, Zhun; Liu, Yuexuan (Frontiers in Oncology, 2023)
Hepatocellular carcinoma (HCC) is one of the most frequent malignancies, with high incidence and mortality. As the majority of HCC patients are diagnosed at an advanced stage and die of recurrence and metastasis, its pathology and new biomarkers are needed. Circular RNAs (circRNAs) are a large subclass of ncRNAs with covalently closed loop structures and abundant, conserved, stable, tissue-specific expression in mammalian cells. CircRNAs exert multiple functions in HCC initiation, growth and progression, serving as promising biomarkers for diagnosis, prognosis and therapeutic targets for this disease. This review briefly describes the biogenesis and biological functions of circRNAs and elucidates the roles of circRNAs in the development and progression of HCC, especially regarding EMT, drug resistance and interactions with epigenetic modifications. In addition, this review highlights the implications of circRNAs as potential biomarkers and therapeutic targets for HCC. We hope to provide novel insight into the roles of circRNAs in HCC.